The Brady-Euro Yield Differential Debate : Why Arbitrage is Infeasible - Kaune Moreno, Federico; Buckberg, Elaine (Washington, D.C. : International Monetary Fund, 1996)
Brady bonds offer substantially higher returns than Eurobonds. This paper examines the Brady and Eurobond markets for developing country debt and finds that the apparent arbitrage opportunity is not only smaller than it at first appears, but is infeasible given the illiquidity of the Eurobond market. The maturity adjusted return differential between Brady and Eurobonds is smaller than the commonly cited yield spreads. Moreover, the transactions costs of executing a Eurobond short contract render arbitrage a loss-making proposition. Given the many crossover investors who are active in both the Brady and Euro markets, why do Eurobond investors not trade them actively?.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet